1995
DOI: 10.1111/j.1365-3083.1995.tb03555.x
|View full text |Cite
|
Sign up to set email alerts
|

A Dysbalanced Immune System in Cryptogenic Lennox‐Gastaut Syndrome

Abstract: In children with cryptogenic Lennox‐Gastaut syndrome we found a functionally impaired humoral immune response to a primary antigen (haemocyanin), despite signs of a triggered immune system consisting of elevated IgG concentrations. This combination of immunological findings, considered to be the expression of a dysbalanced‐triggered as well as functionally impaired‐immune system, has also been described in an auto‐immune disease like systemic lupus erythaematodes in humans, and in genetically epilepsy‐prone ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
2
5
0
1
Order By: Relevance
“…Our group previously reported immunological disturbances in patients with WS and LGS, consisting of impairment in T cell subclasses, T cell functional tests, in vivo skin sensitization tests and immunoglobulin levels and the demonstration of the presence of antibody to brain extract in the sera of WS and LGS children [13][14][15][16][17] . Other authors have described similar findings recently [18][19][20][21] .…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Our group previously reported immunological disturbances in patients with WS and LGS, consisting of impairment in T cell subclasses, T cell functional tests, in vivo skin sensitization tests and immunoglobulin levels and the demonstration of the presence of antibody to brain extract in the sera of WS and LGS children [13][14][15][16][17] . Other authors have described similar findings recently [18][19][20][21] .…”
supporting
confidence: 85%
“…Other alterations such as impaired natural killer cell activity, low CD4+ and high CD8+ lymphocytes, reduction in the CD4+/CD8+ ratio, and decreased C4 complement were also described in epilepsy 29,30 . Impairment in humoral immune response to antigens was reported in children with LGS 21 . All authors agree about the presence of a combined disorder of the immune and the nervous systems.…”
Section: Resultsmentioning
confidence: 99%
“…Van Engelen et al 26 found an increased serum concentration of IgG, but the humoral immune response to hemocyanin was impaired. Otherwise, no specific immunological abnormalities were detected.…”
Section: Other Childhood Epilepsiesmentioning
confidence: 98%
“…associada, em 21% dos casos, a baixos níveis de IgG 35 que, na forma criptogênica, mostra um envolvimento imunológico definido por resposta humoral, funcionalmente alterada, à um antígeno primário (hemocianina) e elevação na concentração de IgG 36 . Ou seja, em termos fisiopatogênicos, NCC e SLG possuem um substrato imunológico para suas manifestações clínicas -na NCC, através de mecanismos complexos, e na SLG, por mecanismos ainda obscuros.…”
Section: Fig 3 Evolução Dos Eegs (Ii) a -Atividade Epileptiforme Tunclassified